The Implementation of MyOrganic: A Case Study of Koperasi ABSB - Hoyaeli, Sabariyah; Othman, Zakirah; Anas, Iswandi; Shafie, Shafini M (UUM Press, 2018)
Rice is a staple food and daily routine for Malaysians. Currently, the increasing population in Malaysia has led to the need to increase rice production with more quality. Therefore, the government established a scheme with national organic standards, MS 1259: 2015 which is myOrganic certification to recognize organic farms. Koperasi ABSB is the first rice farm that obtained this certification. Thus, the aims of this study are to explore the implementation of myOrganic in Koperasi ABSB and the barriers faced by this cooperative to implementing myOrganic certification. Qualitative method is used in this case study through interviews and observation. The finding showed that the implementation of myOrganic is as follows, by register myGAP, register myOrganic, Department of Agricultural Malaysia (DOA) will send a supervisor, prepare nine files or records, perform internal and external audit, and renew myOrganic. This study is expected to increase awareness of organic farming practices and promote the implementation of myOrganic in agriculture industry especially for the new farmer who wants to register and obtain myOrganic certification.